A rare case of anomalous origin of the left anterior descending artery from the pulmonary artery. Issue 6 (22nd April 2019) - Zhang, Yanting; Wang, Bin; Li, Yuman; Xie, Mingxing
Abstract: Anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital heart disease, with an incidence of <1 in 300 000 live births. We describe a rare case of a 23‐month‐old infant admitted for cough and fever. Echocardiography showed a branch of the left coronary artery originating from the pulmonary artery. The coronary computed tomographic angiography revealed anomalous origin of the left anterior descending (LAD) artery from the pulmonary artery with the left circumflex artery and right coronary artery arising normally from the aorta. The infant successfully underwent surgical reimplantation of the LAD to the ascending aorta. Our case emphasizes that echocardiography and computed tomographic angiography are valuable imaging modalities for making an accurate diagnosis and determining the precise surgical plan.